PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM TIPE PEER INSTRUCTION FLIPPED UNTUK MENINGKATKAN SELF-EFFICACY PADA SISWA PRA SEJAHTERA - Lala Nailah Zamnah (Jurnal Pendidikan dan Pengajaran, 2019)
This study aims to examine the improvement of self-efficacy of underprivileged students. The design of this study is a non-equivalent control group involving two classes. The first class obtained learning using Flipped Classroom type Peer Instruction Flipped and the second class obtained conventional learning. The instrument used in this study is a self-efficacy questionnaire. This research was conducted in Class XI in one of the Vocational Schools in Ciamis. Data analysis using the Mann-Whitney test. The results showed that learning using Flipped Classroom type Flipped Peer Instruction had an influence on increasing the self-efficacy of underprivileged students.